2018
DOI: 10.1002/slct.201802235
|View full text |Cite
|
Sign up to set email alerts
|

Deep Eutectic Solvents as a New Generation of Chemical Chaperones

Abstract: Despite research efforts to unravel the role of naturally occurring deep eutectic solvents (NADESs) in living cells, there are still many questions left unanswered. The proposed hypothesis about the role of NADESs in cryopreservation and resistance of cells motivated us to investigate whether DESs might possess chaperoning activity. Accordingly, here, the chaperone‐like activity of a well‐known DES, urea‐choline chloride DES (UC), on a model protein, lysozyme, has been evaluated. The results showed that UC DES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…195 The fact that many DESs contain natural primary metabolites including sugars, sugar alcohols, organic acids, amino acids, and amines (which are thought to aid in survival at negative temperatures) has inspired researchers to begin to explore DESs in innovative ways, such as cryoprotective agents inspired by the NADES-like compounds in plants which help prevent the formation of ice in cells, 196 room-temperature storage media for therapeutic proteins, 197 and as artificial, small-molecule chaperonins aiding in protein refolding. 198 Overall, these results demonstrate that the unique properties of DESs (e.g., low water activity, high ionic strength, molecular crowding, and ultrahigh viscosity) open exciting possibilities for controlling nucleic acid structure, stability, and for deploying catalytic, biosensory, and enzyme−nucleic acid complexes within DESs. We refer interested readers to more detailed accounts on this topic published previously.…”
Section: Genomics/fundamentals Of Nucleic Acidsmentioning
confidence: 72%
See 1 more Smart Citation
“…195 The fact that many DESs contain natural primary metabolites including sugars, sugar alcohols, organic acids, amino acids, and amines (which are thought to aid in survival at negative temperatures) has inspired researchers to begin to explore DESs in innovative ways, such as cryoprotective agents inspired by the NADES-like compounds in plants which help prevent the formation of ice in cells, 196 room-temperature storage media for therapeutic proteins, 197 and as artificial, small-molecule chaperonins aiding in protein refolding. 198 Overall, these results demonstrate that the unique properties of DESs (e.g., low water activity, high ionic strength, molecular crowding, and ultrahigh viscosity) open exciting possibilities for controlling nucleic acid structure, stability, and for deploying catalytic, biosensory, and enzyme−nucleic acid complexes within DESs. We refer interested readers to more detailed accounts on this topic published previously.…”
Section: Genomics/fundamentals Of Nucleic Acidsmentioning
confidence: 72%
“…As an additional example, Marrucho and co-workers recently introduced a DES comprising a 1:1 molar mixture of choline chloride with acetic acid as a promoter of fast lysozyme fibrillation . The fact that many DESs contain natural primary metabolites including sugars, sugar alcohols, organic acids, amino acids, and amines (which are thought to aid in survival at negative temperatures) has inspired researchers to begin to explore DESs in innovative ways, such as cryoprotective agents inspired by the NADES-like compounds in plants which help prevent the formation of ice in cells, room-temperature storage media for therapeutic proteins, and as artificial, small-molecule chaperonins aiding in protein refolding . Overall, these results demonstrate that the unique properties of DESs ( e.g.…”
Section: Selected Applications Of Deep Eutectic Solventsmentioning
confidence: 99%
“…Monitoring of the intrinsic fluorescence of tryptophan confirmed that the solvents promoted correct refolding. The biological activity of the enzyme, again measured by the ability to lyse bacteria, was also recovered better when the solvent was present in the renaturation solution (Niknaddaf et al, 2018).…”
Section: The Influence Of Choline-based Ionic Liquids On the Catalytic Activity Of Lipase Frommentioning
confidence: 97%
“…In living cells, protein folding and re-folding is facilitated by other proteins known as chaperones that play an important role in the response of the cell to stress. The fact that many of the components of deep eutectic solvents are found in cells and are related to survival under extreme condition led Niknaddaf et al to put forward the hypothesis that these solvents could act as chemical chaperones (Niknaddaf et al, 2018). They conducted experiments to test this using a model of lysozyme aggregation by the reducing agent dithiothreitol.…”
Section: The Influence Of Choline-based Ionic Liquids On the Catalytic Activity Of Lipase Frommentioning
confidence: 99%
“…13,14 Due to these properties, ILs have begun to supersede conventional organic solvents. 15,16 Nonetheless, ILs suffer from several limitations such as costly synthesis, toxicity and challenging preparation besides having potential environmental impacts. 16…”
Section: Introductionmentioning
confidence: 99%